School security : how to build and strengthen a school safety program - Timm, Paul (Butterworth-Heinemann, 2021)
School Security: How to Build and Strengthen a School Safety Program, Second Edition emphasizes a proactive rather than reactive approach to school security. Readers are introduced to basic loss prevention and safety concepts, including how to communicate safety information to students and staff, how to raise security awareness, and how to prepare for emergencies. The book discusses how to positively influence student behavior, lead staff training programs, and write sound security policies. As school safety challenges continue to evolve with new daily stories surrounding security lapses, lockdowns, or violent acts taking place, this thoroughly revised edition will help explain how to make educational institutions a safer place to learn. The book includes new tabletop exercises for managing emergencies Contains coverage of the new risks commonly facing schools today, from access control to social media. It presents updated school security resources and serves as a comprehensive guide for building an effective security program at little or no cost. The book also covers fundamental CPTED concepts, addresses bullying, teen suicide, harassment, and dating violence and takes a holistic approach to school security rather than focusing on a particular threat or event.